6-Deoxyjacareubin, a natural compound preventing hypoxia-induced cell death, ameliorates neurodegeneration in a mouse model of familial amyotrophic lateral sclerosis. (February 2021) - Hoshino, Tomonori; Matsuzawa, Shu-ichi; Takahashi, Ryosuke
Highlights: 6-Deoxyjacareubin suppressed hypoxia-induced cell death via non-apoptotic pathway. Early 6-deoxyjacareubin administration prolonged survival time in familial ALS model. 6-Deoxyjacareubin attenuates motor neuron loss and glial activation. 6-Deoxyjacareubin may be a therapeutic strategy for hypoxia-related neurodegeneration. Abstract: The central nervous system (CNS) uses a significant amount of oxygen for energy production. Decreased oxygen supply due to impaired blood supply critically damages the CNS. As chronic hypoxic conditions have diverse effects via the excessive production of reactive oxygen species, protection from hypoxic damage is important for cell survival. Recent studies have revealed that various markers of hypoxia are altered in age-related neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS), indicating the involvement of hypoxia. However, therapeutic strategies targeting hypoxia-induced pathways in ALS have not been developed yet. We previously screened small-molecule compounds that inhibit hypoxia-induced cell death and identified 6-deoxyjacareubin. We hypothesized that the modulation of hypoxia signaling by 6-deoxyjacareubin might protect motor neurons in ALS. Here, we show that 6-deoxyjacareubin indeed ameliorates neurodegeneration in a mouse model of familial ALS. Administration of 6-deoxyjacareubin to this familial ALS model significantly attenuated disease progression and improved locomotor dysfunction. We also found that 6-deoxyjacareubin reduced motor neuron loss and glial activation. Our results indicate that 6-deoxyjacareubin might serve as a potential therapeutic tool for ALS. Moreover, these results suggest that modulation of hypoxia signaling pathways provides a promising strategy to develop therapies for other types of neurodegenerative diseases also characterized by hypoxia.